Proof of concept for the use of wearable sensors to monitor women and men's workload and mobility in Indonesian agricultural communities - Stewart, Timothy (Palladium Group, 2019)
Presented by Timothy Stewart (Palladium Group), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.